Study on diffusivity of Gallium dopant in Silicon using Spin On Dopant (SOD) technique - Mohd Rosydi Zakaria (Universiti Malaysia Perlis, 2008)
Diffusion and ion implantation are two major processes by which chemical species or dopant are introduced into a semiconductor such as silicon to form the electronic structure. The diffusion process is a method to control the thermal budget to expand performance device by combination of temperature and time. In this project the diffusivity of gallium using spin on dopant technique is studied. The study includes mathematical calculation, computer simulation, fabrication and characterization of the diffusivity criteria such as surface concentration, dopant profiling and resistivity. The process starts with pre-deposition and drive-in at various temperature and time. The affect of the parameters are then characterized using MiniSims and Four Point Probes to determine the junction depth, depth profiling and resistivity. The Spreading resistance profile (SRP) is then used to characterize the junction depth and concentration as comparison to the result obtained from MiniSim. The result shows that the junction depth and resistivity increased with the increase of temperature and longer exposure times in furnace. From the depth profiling results, it shows the existence of gallium mass in the silicon substrate with some contaminants. The results from experimental are found comparable with theoretical and simulation.